The Effect of Daily Living Activities of the Elderly Suffering from Hip Fractures - Huda Farouk Mohamed; Sahar Ahmed Shafik; Amany Mohamed Saad (Indonesian Journal of Global Health Research, 2022)
Elderly in the world is expected that are double by 2050 and triple by 2100, Elderly who suffer from hip fractures must have tasks and routines that are performed on a daily basis in order to live independently, being able to successfully manage routine tasks. Assess daily living activities of the elderly suffering from hip fractures. Descriptive research design was used. Purposive sample include 200 elderly. The study results revealed that more than two thirds of elderly have unsatisfactory knowledge; nearly two fifths of elderly were partially dependent in doing daily living activities. There was highly statistically significant correlation between elderly total knowledge and total daily living activities. Less than two fifths of elderly were partially dependent in doing their activities and more than three fifths of elderly have unsatisfactory knowledge about hip fractures. Also, there was a positive relation between elderly total knowledge about hip fractures and total daily living activities with highly statisticallysignificantcorrelation.